Multiparameter analysis of stimulated human peripheral blood mononuclear cells: A comparison of mass and fluorescence cytometry - Nicholas, Katherine J.; Greenplate, Allison R.; Flaherty, David K.; Matlock, Brittany K.; Juan, Juan San; Smith, Rita M.; Irish, Jonathan M.; Kalams, Spyros A. (Cytometry. Part A, 2016)
Mass and fluorescence cytometry are quantitative single cell flow cytometry approaches that are powerful tools for characterizing diverse tissues and cellular systems. Here mass cytometry was directly compared with fluorescence cytometry by studying phenotypes of healthy human peripheral blood mononuclear cells (PBMC) in the context of superantigen stimulation. One mass cytometry panel and five fluorescence cytometry panels were used to measure 20 well‐established lymphocyte markers of memory and activation. Comparable frequencies of both common and rare cell subpopulations were observed with fluorescence and mass cytometry using biaxial gating. The unsupervised high‐dimensional analysis tool viSNE was then used to analyze data sets generated from both mass and fluorescence cytometry. viSNE analysis effectively characterized PBMC using eight features per cell and identified similar frequencies of activated CD4+ T cells with both technologies. These results suggest combinations of unsupervised analysis programs and extended multiparameter cytometry will be indispensable tools for detecting perturbations in protein expression in both health and disease. © 2015 International Society for Advancement of Cytometry